1989
DOI: 10.1093/oxfordjournals.alcalc.a044872
|View full text |Cite
|
Sign up to set email alerts
|

Determinations of Ethanol, Acetaldehyde and Acetate in Blood and Urine During Alcohol Oxidation in Man

Abstract: Blood and urine samples were analyzed for ethanol, acetaldehyde and acetate during alcohol oxidation in Japanese men by head space gas chromatography, following the consumption of 16 ml/kg of beer during a 20 min period. The maximum level of blood/urine ethanol was found to be 15-17 mM (20-22 mM), while that of acetaldehyde in a flusher and in non-flushers was 20 microM (52 microM) and 2-5 microM (10-13 microM), respectively. Acetate levels in these groups ranged from 0.2 mM (0.1 mM) to 0.8 mM (1.0 mM). Blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…Transgenic mice with cardiac overexpression of alcohol dehydrogenase (ADH) 1 displayed higher cardiac acetaldehyde levels associated with compromised heart function at whole heart and ventricular myocyte levels following alcohol intake (10 -12), suggesting that acetaldehyde may be one of the major culprits for alcoholic cardiomyopathy and possibly other alcoholic complications. Blood acetaldehyde levels may reach low millimolar range following alcohol intake in Asians and African Americans due to defective aldehyde dehydrogenase (ALDH) (13,14), making these populations at higher risk for alcohol-induced tissue and cell injury. To further elucidate the culprit role of acetaldehyde in tissue and cell damage, our present study was designed to produce a transgene construct-encoding human ALDH type 2 isozyme (ALDH2) to be overexpressed in human umbilical vein endothelial cells (HUVECs).…”
mentioning
confidence: 99%
“…Transgenic mice with cardiac overexpression of alcohol dehydrogenase (ADH) 1 displayed higher cardiac acetaldehyde levels associated with compromised heart function at whole heart and ventricular myocyte levels following alcohol intake (10 -12), suggesting that acetaldehyde may be one of the major culprits for alcoholic cardiomyopathy and possibly other alcoholic complications. Blood acetaldehyde levels may reach low millimolar range following alcohol intake in Asians and African Americans due to defective aldehyde dehydrogenase (ALDH) (13,14), making these populations at higher risk for alcohol-induced tissue and cell injury. To further elucidate the culprit role of acetaldehyde in tissue and cell damage, our present study was designed to produce a transgene construct-encoding human ALDH type 2 isozyme (ALDH2) to be overexpressed in human umbilical vein endothelial cells (HUVECs).…”
mentioning
confidence: 99%
“…However, this issue seems to be irrelevant concerning the pharmacokinetic interaction of 1,4-BD and EtOH, because an increase of GHB formation was not observed if both drugs were incubated. Furthermore, an in vivo accumulation of AL, which could theoretically increase GHB formation, seems unlikely due to the fast degradation of AL (Eriksson 1983;Tsukamoto et al 1989). If an increase of total reaction rate was observed, the slower of both reactions must have been accelerated here.…”
Section: Discussionmentioning
confidence: 93%
“…This suggests that the first step of 1,4-BD metabolism is rate limiting. This issue is known for EtOH metabolism as well, on the condition that there is no ALDH deficiency (Eriksson 1983;Tsukamoto et al 1989). Therefore, and according to Poldrugo et al, it can be concluded that the estimated enzyme kinetic parameters represent the kinetic of the first step of 1,4-BD metabolism catalyzed by ADH (Poldrugo and Snead 1986).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, after alcohol drinking, a specific amount of acetaldehyde is maintained and sustained in the body for several hours because EtOH may be a resource for it. To avoid the problems associated with degradation and maintain effective concentrations of acetaldehyde in the body, which are both experimentally and clinically similar to the concentrations following EtOH administration (or drinking) [34], [38], the ALDH inhibitors cyanamide and disulfiram are administered in combination with EtOH or acetaldehyde [39]. The combination of acetaldehyde and cyanamide induced water and salt intake in contrast to acetaldehyde alone [16].…”
Section: Acetaldehyde Induces Thirst Sensationmentioning
confidence: 99%